1997
DOI: 10.1099/00221287-143-7-2381
|View full text |Cite
|
Sign up to set email alerts
|

Tn5-induced lipopolysaccharide mutations in Bordetella pertussis that affect outer membrane function

Abstract: An LPSB-specific mAb was used to screen for ten TnS insertion mutants of Bordetella pertussis which have LPS which is phenotypically distinct from either wild-type LPSAB or LPSB. Silver-stained SDS-PAGE gels showed nine different LPS phenotypes, six of which contain two clinically undocumented LPS bands, designated lntA and lntB based on their proximity to the LPSA and LPSB bands, respectively. Binding assays with LPSA-and LPSB-specif ic mAbs established changes in epitope exposure for the various mutant LPS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…A number of mutations have been introduced into this operon, leading to the generation of mutant strains lacking one, two, or all three of the terminal sugars. WlbH lacks the terminal sugar (17,18), MLT7 appears to lack the last two sugars (19), and WlbG and WlbL lack all three sugars (17,18). Homology studies have suggested that WlbL fails to produce the first sugar in the trisaccharide, while WlbG retains the ability to produce this sugar, but fails to transfer it to the surface of the bacterial cell (18).…”
Section: S Urfactant Protein a (Sp-mentioning
confidence: 99%
“…A number of mutations have been introduced into this operon, leading to the generation of mutant strains lacking one, two, or all three of the terminal sugars. WlbH lacks the terminal sugar (17,18), MLT7 appears to lack the last two sugars (19), and WlbG and WlbL lack all three sugars (17,18). Homology studies have suggested that WlbL fails to produce the first sugar in the trisaccharide, while WlbG retains the ability to produce this sugar, but fails to transfer it to the surface of the bacterial cell (18).…”
Section: S Urfactant Protein a (Sp-mentioning
confidence: 99%
“…Examples include the genes and operons that encode a motility apparatus (2, 3), the pertussis toxin (7), and possibly a type III secretion system (28, 29). These differentially expressed factors are likely to contribute to subspeciesspecific characteristics such as host specificity and the ability to cause pathology and to persist.The lipopolysaccharide (LPS) molecules expressed on the surface of B. pertussis, B. parapertussis, and B. bronchiseptica also differ substantially (4,5,17,23). The observation that LPS structures are regulated by the BvgAS virulence control system suggests that these molecules play a role in respiratory tract infection (16,17).…”
mentioning
confidence: 99%
“…The lipopolysaccharide (LPS) molecules expressed on the surface of B. pertussis, B. parapertussis, and B. bronchiseptica also differ substantially (4,5,17,23). The observation that LPS structures are regulated by the BvgAS virulence control system suggests that these molecules play a role in respiratory tract infection (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule plays a major role in the host-pathogen interactions (46) and is responsible for endotoxic activities similar to those of enteric bacteria (1,50). (4), which consist of a lipid A moiety linked to a core nonasaccharide or a dodecasaccharide.…”
mentioning
confidence: 99%